Integrating Artificial Intelligence and Big Data in Spanish Journalism Education: A Curricular Analysis - Santiago Tejedor; Laura Cervi; Luis M. Romero-Rodríguez; Stephanie Vick (Journalism and Media)
Artificial intelligence (AI) and big data have impacted different professional sectors in our society. Communication and journalism are clearly among them. From the automatic generation of content to the identification of topics of interest or monitoring of users’ usage habits, AI introduces important training challenges for professionals in the field of communication. Meanwhile, big data analytics enables data journalists to handle large amounts of information in an automated manner, allowing them to perform in-depth analysis of disorganized data. This study analyzes the integration of artificial intelligence (AI) and big data in the curricula of journalism degrees offered by Spanish universities. The research employs quantitative and qualitative methods to examine the typology, syllabus, and distribution of subjects directly or indirectly addressing AI and big data topics, based on indicators such as structure, credit system, objectives, competencies, and professional profiles. The results reveal a scarce integration of AI and Big Data subjects in journalism curricula in Spain. Among the analyzed courses, only seven addressed data journalism as a complete course, while 19 introduced AI and Big Data as part of more general content. The study highlights the need for journalism education to adapt to the disruptive impact of AI and big data on the profession. It discusses the debate between focusing on teaching technological skills versus providing critical and ethical values. The research aims to contribute to the discussion on the readiness of journalism curricula to cope with technological advancements by analyzing the Spanish case.